Bipolar behavior revealed by D-pi-D chromophores bearing dithienothiophene (DTT) as pi-center in redox- and LE properties - Kim, OK; Woo, HY; Kim, JK; Heuer, WB; Lee, KS; Kim, CY (ELSEVIER, 2002)
A series of D/D- and D/A pair conjugated chromophores based on dithienothiophene, DTT, as conjugated linker (pi-center) were synthesized (D-pi-D and D-pi-A) and studied optical and electrochemical properties. Unusual bipolar behavior was observed with D-pi-D, displaying the redox property similar to that of D-pi-A. Single-layer lightemitting (LE) devices fabricated with such electronically dissimilar oligomers exhibited a close resemblance in their diode characteristics that are commonly observed with bipolar LE materials. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: NONLINEAR-OPTICAL CHROMOPHORES; CONJUGATED POLYMERS; BRIDGING LIGANDS; ELECTRON; THIOPHENE